Applying the 5 Why Method to Verification of Non-Compliance Causes Established after Application of the Ishikawa Diagram in the Process of Improving the Production of Drive Half-Shafts - Dziuba, Szymon
Zlepšenie výrobného procesu hnacích polovičných hriadeľov. Overovanie príčin nesúladu zistené pomocou Ishikawovho diagramu s použitím metódy 5WHY a brainstormingu.